Faktor Sosial Ekonomi yang Berhubungan dengan Permintaan Bawang Merah Di Kecamatan Amuntai Selatan Kabupaten Hulu Sungai Utara - Arief Hidayatullah; Riswandi Riswandi (Rawa Sains: Jurnal Sains STIPER Amuntai, 2011)
This study aims to (i) determine the magnitude of demand for shallots by households in Amuntai Selatan Subdistrict, (ii) find out the amount of expenditure for shallot demand by households in South Amuntai Subdistrict and (iii) to know the effect of socio-economic factors on the demand by households in the Amuntai Selatan District. This research was carried out in six villages in Amuntai Selatan District, namely Kota Raja, Jumba, Murung Sari, Mamar, Paring Bay and Cempaka using cluster random sampling multistage way. Based on the results of the study, the average demand for shallots by households is 1.44 kg / month. Expenditures for demand for shallots in a month is Rp. 8,338.33 or 0.52% of total family income. From the results of correlation analysis and t-test there is a significant relationship between the level of demand for shallots with the number of family members and tastes, while family income factors, prices of shallots, formal education level of housewives, age of housewives and areas of origin of housewives are not has a significant relationship to the demand for shallots. Path analysis was obtained, that variable was total family income, variable price of shallots, variable number of family members, variable level of education of housewives, variable age of housewives, regional variables of origin of housewives, and variable tastes of housewives had a total effect on demand Red onion